1972
DOI: 10.1002/1097-0142(197212)30:6<1616::aid-cncr2820300630>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic management of the hormone-secreting endocrine malignancies

Abstract: The medical management of metastatic endocrine tumors, such as malignant insulinoma, adrenal carcinoma, and malignant carcinoid, involves the use of both anticancer and antihormonal chemotherapy. The former is directed against the primary tumor and its metastases, while the latter offers palliation through the inhibition of synthesis, release, or direct cellular action of the specific secretory product. The current clinical results with the use of streptozotocin in malignant insulinoma, and o,p′DDD in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Biochemical ,, and pharmacological studies of SZT have been reported. SZT has been used clinically , to treat malignant islet cell carcinoma of the pancreas and carcinoid carcinoma, but the clinical use has been limited 349 because of the damage to the pancreas and kidneys. A review was published which covers the chemical and biological aspects of streptozotocin.…”
Section: Carbohydrate Analogs1 Historical Backgroundmentioning
confidence: 99%
“…Biochemical ,, and pharmacological studies of SZT have been reported. SZT has been used clinically , to treat malignant islet cell carcinoma of the pancreas and carcinoid carcinoma, but the clinical use has been limited 349 because of the damage to the pancreas and kidneys. A review was published which covers the chemical and biological aspects of streptozotocin.…”
Section: Carbohydrate Analogs1 Historical Backgroundmentioning
confidence: 99%
“…For reducing the high and dangerous serum insulin values, several types of pharmacologically active substances have been tested. These include insulin-reducing agents such as corticosteroids, glucagon, human growth hormone and diazoxide and anti-cancer agents such as tubercidin (7deazaadenosine), 5-fluorouracil, alloxan, L-asparaginase, nitrogen mustard iind streptozotocin (14,15).…”
mentioning
confidence: 99%